If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(5x) = 6 Remove parenthesis around (5x) ln * 5x = 6 Reorder the terms for easier multiplication: 5ln * x = 6 Multiply ln * x 5lnx = 6 Solving 5lnx = 6 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Divide each side by '5nx'. l = 1.2n-1x-1 Simplifying l = 1.2n-1x-1
| 9x^4-20x^2-21=0 | | -4(7x-4)=-292 | | r^2-7r-6=0 | | Z^2(4z^4+z^3-11z^2-6)= | | -3c=-21 | | 0.7w-0.5w+0.3w=4 | | k-2=7-5k | | (x-3)-(2x-1)= | | -4x^2+16x+48=0 | | (4x+1)+(2x-2)-(2x-1)= | | 6(x+2)=x+8 | | 4-c=3 | | 12+c=5 | | 2x^2+16x+30=0 | | -1=x-5 | | 9x-17x=24 | | 4+1000000000000000000000000= | | 8+x=7 | | 5(x+5)=x+6 | | y^2+8y=-13 | | -3x=-6 | | 8-12x=6times(1+x) | | X-3(4)=2X+8 | | 98x^2-50=0 | | 5x^2+6x-17=37-33x | | -2x^2+10x-5=0 | | 3(y+8)=5y+24 | | 3x^3+2x^2-5x=0 | | 400+20x=600+10x | | =-16(n-1)9 | | 2x^2+12x+36=68 | | -3d=-12 |